2019
DOI: 10.1002/bmc.4465
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carbenoxolone by ultra‐high‐performance liquid chromatography tandem mass spectrometry in mouse brain and blood after systemic administration

Abstract: Carbenoxolone is a derivative of glycyrrhetinic acid found in the root of Glycyrrhiza glabra, colloquially known as licorice. It has been used as a treatment for peptic and oral ulcers. In recent years, carbenoxolone has been utilized in basic research for its ability to block gap junctional communication. Better understanding the distribution of carbenoxolone after systemic administration can lead to a better understanding of its potential sites of action. Presented is an ultra high‐performance liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several research showed that some saponins in GRR [ 55 , 56 ], GRP [ 57 ], and phthalides in ASR [ 58 , 59 ] can be absorbed into the cerebrospinal fluid. In addition, saponins in GRR [ 60 ] and GRP [ 61 ], flavonoids in ZSS [ 62 ], and source esters in PRP [ 53 ] have been determined in the brain tissue homogenate. In this research, 10 prototypical components and 6 metabolites were preliminarily characterized in the rat cerebrospinal fluid after oral administration of Qi-Fu-Yin.…”
Section: Discussionmentioning
confidence: 99%
“…Several research showed that some saponins in GRR [ 55 , 56 ], GRP [ 57 ], and phthalides in ASR [ 58 , 59 ] can be absorbed into the cerebrospinal fluid. In addition, saponins in GRR [ 60 ] and GRP [ 61 ], flavonoids in ZSS [ 62 ], and source esters in PRP [ 53 ] have been determined in the brain tissue homogenate. In this research, 10 prototypical components and 6 metabolites were preliminarily characterized in the rat cerebrospinal fluid after oral administration of Qi-Fu-Yin.…”
Section: Discussionmentioning
confidence: 99%
“…The carbenoxolone (CBX) molecule is polar and relatively large, so it has very poorly crossing the blood–brain barrier [ 42 ]. Other studies show that CBX does not cross the blood–brain barrier at all [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…This applies to both intraperitoneal and intravenous CBX. In addition, CBX is metabolized differently in different parts of the body, and together produces a large number of different metabolites [ 42 ]. In any case, the system administration of CBX is inadequate for studying the effects on the targets in the central nervous system.…”
Section: Methodsmentioning
confidence: 99%